Why do individuals seek out adventure sport coaching?. Issue 3 (2nd July 2020) - Eastabrook, Chris; Collins, Loel
ABSTRACT: Individualisation is a key aspect of coaching practice. This is particularly important for adventure sport coaches, given the demands of the hyper-dynamic coaching environment and the various motivations to participate in adventure sports. However, the literature on individualisation is limited. As a logical beginning, the aim of this study is to understand why individuals seek coaching in the context of adventure sports. Semi-structured interviews with adventure sport clients (N = 15) were thematically analysed, revealing that clients seek three different but not mutually exclusive experiences: holistic, authentic, and developmental. Importantly, the extent to which each experience was desired varied between individuals. These differences in individual desires place a fundamental emphasis on coaches' understanding of why an individual seeks coaching as well as their longer-term participation goals, and then having the adaptive expertise to meet those expectations. Further research is required to understand how aspects of the developmental experience are achieved, specifically in the desired contexts.